The Effect of Eyestalk Ablation on Several Immunologic Variables in Litopenaeus vannamei - Indriyani Nur; Hartina Iyen; Yusnaini Yusnaini (Department of Aquaculture, 2021)
Eyestalk ablation inflicted upon crustacean is generally performed in captivity to induce ovarian maturation. However, ablation is a hurtful action that may impose physiological stress and even affects survival. The immunologic repercussions of the ablation have not been well understood and thus this study aims to analyze the effect of ablation on immunologic variables through comparing the ablated Litopenaeus vannamei with those of unablated shrimps (control). Unilateral left eyestalk ablation was inflicted on shrimp samples. Shrimp immune responses were observed based on the Total Haemocyte Count (THC), Differential Haemocyte Count (DHC) composing of hyaline cell (HC) counts and granular cell (GC) counts, glucose and uric acid levels, along with the weight gains of shrimps. Observed parametres were taken twice from 10 shrimps for each of the observed and control samples (i.e., on 6 h and 5 d elapsed time). The results show that the ablated shrimps group, after 6 h elapsed time, experienced significant decrease in THC (3.12 ± 0.75 x 106 cells ml-1), but recovered after 5 days (3.89 ± 0.96 x 106 cells ml-1) and were not significantly different from the control (5.16 ± 2.20 x 106 cells ml-1). Meanwhile, glucose level show significant decrease over 6 h and 5 d post ablation (108 and 93 mg dL-1, respectively) compared to the resulting responses from the control (35-36 mg dL-1). Differences in DHC for all cell types as well as uric acid in hemolymph were not significant between the observed and the control samples. Moreover, the ablated treatment did not affect the growth of vannamei after 5 d post ablation. The results revealed that changes occur on the physiological and immune parameters of shrimps due to the eye ablation treatment as shown by the decrease in the THC and glucose levels, especially within the early moments post treatment. However, at the end of the observation (5 d post ablation), shrimps exhibit signs of recovery from stress indicated by an increase in THC close to normal.